Dermatologist, orthopaedist, and psychiatrist walk into a COVID ward: on the permeability of professional boundaries in a competition-free context. - Rys, Maciej; Krzyworzeka, Paweł; Żukowicka-Surma, Anna (Innovation: The European Journal of Social Sciences, 2024)
In studies on professions, it has long been understood that relations between professions are charged with competition over jurisdictions. The literature describes several techniques, such as rhetorical boundary-work, that professionals use to expand jurisdictions, gain a monopoly, or protect autonomy. But there still needs to be discovered how professionals cooperate when they are not motivated or threatened by jurisdictional struggle. In this article, we offer an analysis of COVID-19 wards in Poland, where physicians from diverse specialisations were made to work together and treat patients with coronavirus disease. That allows us to expand theoretical debate about professions by showing that in a context free of competition, boundaries between professions become permeable.